Baron Coastal Management Strategy in Efforts to Realize Sustainable Ecotourism-Based Coastal Management - Rokhmatul Umaroh; Sri Rahayu Budiani; Rika Harini (Indonesian Journal Publisher, 2026)
Baron Beach is one of the main coastal tourist destinations in Gunungkidul Regency, which, since its early development, has functioned as a center for tourism and local fishing activities. The high intensity of tourist visits can put pressure on the coastal environment if a sustainable management system does not balance it. This study aims to formulate a sustainable ecotourism-based coastal management strategy for Baron Beach by integrating environmental conservation, local community empowerment, environmentally friendly infrastructure development, tourist education, and monitoring and evaluation, all grounded in the area's carrying capacity. The research methods included field observations, structured interviews with managers and local communities, and the distribution of questionnaires to tourists. Environmental quality analysis was conducted by measuring Total Suspended Solids (TSS), pH, Dissolved Oxygen (DO), and Biological Oxygen Demand (BOD) in accordance with APHA (2023) standards. Management strategies were formulated using SWOT analysis and prioritized using the Analytic Hierarchy Process (AHP). The results of the study indicate that the water quality of Baron Beach still meets the quality standards for pH, DO, and BOD, but the TSS value is very high and has the potential to degrade the coastal ecosystem. The involvement of the local community in tourism activities is relatively high, but there is still a need to increase capacity and strengthen environmental education. The SWOT–AHP analysis results indicate that the Strengths–Opportunities (S–O) strategy is a top priority in the management of Baron Beach. This study emphasizes the importance of implementing ecotourism-based coastal management supported by a sustainable monitoring and evaluation system to maintain a balance between environmental conservation and community welfare.